Chronic systemic capillary leak syndrome with lymphatic capillaries involvement and MYOF mutation: case report and literature review - Gao, Dehua; Zhong, Wen; Zhang, Weiru; Wang, Xuan; Li, Weiping; Liu, Jun (Frontiers in Genetics, 2023)
Introduction: Idiopathic systemic capillary leak syndrome (SCLS) is a rare disorder characterized by hemoconcentration, hypoproteinemia and edema. Chronic SCLS (cSCLS) presents as intractable edema, distinguishing it from the classic acute form, and only about 10 cases were reported worldwide. Nevertheless, the underlying pathogenesis of both types is obscure. Case presentation: We report a case of a 58-year-old man with chronic edema persisting for 8 years, complicated by unique chylous polyserous effusions and hypotrichosis, which was successfully relieved by treatment with dexamethasone, intravenous immunoglobulin, and thalidomide. Furthermore, a variant c.5594A>G (p.K1865R) in the MYOF gene was identified as a potentially pathogenic mutation through whole-exome genetic sequencing. The proposed mechanism involves its impact on VEGF signaling, leading to increased capillary permeability. Conclusion: Our case illustrates possible lymphatic capillaries involvement in SCLS, which may plays a potential role in immune disorder, and revealed a possible causative genetic mutation of SCLS.